Roll coated large area ITO- and vacuum-free all organic solar cells from diketopyrrolopyrrole based non-fullerene acceptors with molecular geometry effects. Issue 47 (26th April 2016) - Brandt, Rasmus Guldbæk; Zhang, Fei; Andersen, Thomas Rieks; Angmo, Dechan; Shi, Minmin; Gurevich, Leonid; Krebs, Frederik C.; Andreasen, Jens Wenzel; Yu, Donghong
Abstract : We investigate three diketopyrrolopyrrole based small molecular non-fullerene acceptors with molecular geometry effect on mainly their PV performance of both spin-coated ITO based and roll coated large area, ITO- and vacuum-free organic solar cells. Abstract : In this paper, we investigate three diketopyrrolopyrrole (DPP) based small molecular non-fullerene acceptors, namely Ph(DPP)3, Ph(DPP)2, and PhDMe(DPP)2, focusing on molecular geometry effects on the frontier orbital level, light absorption, molecular configuration, electron mobility, thin film morphology, and photovoltaic performance of both spin-coated ITO based and roll coated large area, ITO- and vacuum-free organic solar cells (OSCs). For spin-coated devices based on P3HT as the donor polymer the solar cells gave power conversion efficiencies (PCEs) in the following order for (P3HT:PhDMe(DPP)2, 0.65%) > (P3HT:Ph(DPP)2, 0.48%) > (P3HT:Ph(DPP)3, 0.31%). All devices present an open circuit voltage ( V oc ) higher than 1.0 V. For the roll-coated devices, the PCEs were found to fall in another order and with lower values (P3HT:Ph(DPP)3, 0.54%) > (P3HT:Ph(DPP)2, 0.43%) > (P3HT:PhDMe(DPP)2, 0.04%) and the highest V oc was 0.82 V. Our preliminary results highlight the influence of geometry, structure and processing on the performance of non-fullerene acceptors.